On the parabolic potentials in degenerate-type heat equation. (1991) - Malyshev, Igor
Abstract : Using distributions theory technique we introduce parabolic potentials for the heat equation with one time-dependent coefficient (not everywhere positive and continuous) at the highest space-derivative, discuss their properties, and apply obtained results to three illustrative problems. Presented technique allows to deal with some equation of the degenerate/mixed type.